Ecological momentary assessment of eating and dietary intake behaviors in children and adolescents: A systematic review of the literature. (1st January 2020) - Mason, Tyler B.; Do, Bridgette; Wang, Shirlene; Dunton, Genevieve F.
Abstract: The objective of this review was to summarize associations between ecological momentary assessment (EMA)-measured contextual factors and eating and dietary intake behaviors in children and adolescents. The inclusion criteria were availability of the study in English and use of EMA to study eating and dietary intake behaviors among children and/or adolescents (ages<18). Literature searches were conducted in PsycInfo and PubMed databases across all dates until December 2018. A modified Checklist for Reporting EMA Studies was used to assess quality of studies. Eighteen articles from 15 independent studies were included in the systematic review. Contextual factors examined in relation to children's eating in studies included affect and stress; cognitive factors; social and environment factors; behavioral factors; and caregiver-related factors. Studies suggested there is strong evidence that cognitive and social factors have an effect on eating and dietary intake behaviors while the association between affect and eating and dietary intake behaviors remains mixed. Future studies should consider timing of effects, measure choice, individual difference and contextual factors, and developmental context.